The Question of External Integration of Jurisprudence in the Context of its Political Character (Studia Prawnicze / The Legal Studies, 2019)
The paper analyzes methodological determinants of jurisprudence, indicating several problems in the process of its integration with other sciences; the complex internal structure of jurisprudence and difficulty in meeting the requirements of the general-methodological naturalistic paradigm are considered sources of problems. According to the author, it is more appropriate to define integration as seeking links between theory of law and theories of related disciplines, which is the easiest in respect of political sciences and sociology (postulate of the political character of the law and the science of law). This is because of similar methodological determinants and commonly analyzed phenomena, as well as shared contemporary challenges. The author considers the process of mere transposition of methods and/or concepts developed in other disciplines to be an overly simplified vision of external integration.